Macromineral consumption by Pleurotus ostreatus var. Florida in different straws - Iossi, Matheus R.; Vieira Júnior, Wagner G.; Caitano, Cinthia E. C.; da Silva Alves, Lucas; Palú, Isabela de A.; Heinrichs, Reges; Pardo-Giménez, Arturo; Zied, Diego C. (Archives of Biological Sciences, 2023)
Paper description: Understanding mineral dynamics in agricultural wastes is essential for the successful production of Pleurotus Yields and N, P, K, Ca, Mg, S contents in rice, brachiaria and wheat straw were evaluated. Rice straw produced a greater harvest than wheat and brachiaria straw. Mg correlated with a higher number of mushrooms, while K correlated with a better yield (1st flush). These findings will serve as a guide for the management of Pleurotus ostreatus crop supplementation in agricultural wastes. The results will be useful to improve yields and sustainability. Abstract: Organic agricultural waste is successfully used in the production of mushrooms as it promotes the reuse of resources and increases food production. For the formulation of the substrate for Pleurotus spp. production, the availability of nutrients must be rigorously analyzed to assess whether supplementation is necessary. The aim of this paper was to evaluate the agronomic behavior of Pleurotus ostreatus var. Florida when grown on different straws and to analyze nutrient dynamics at the beginning and end of cultivation. Straws of rice, wheat and brachiaria were used as substrates without any supplementation. The yields, biological efficiency, number and weights of mushrooms were evaluated in two crop cycles. Rice straw provided a higher yield, better biological efficiency and a greater number of mushrooms in both cultures. Wheat straw showed intermediate results for the same variables. None of the substrates showed a significant difference for mushroom weight. In the first crop, only Mg and the number of mushrooms exhibited a positive correlation; in the second crop, only K and the yield of the 1st flush showed a positive correlation. With this study, it was possible to demonstrate that agricultural residues with higher levels of K increase P. ostreatus yield, and that Mg management affects the number of mushrooms for harvesting. The results will be a useful guide for efficient and sustainable mineral supplementation of the substrate.